2017
DOI: 10.1073/pnas.1619928114
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-level genome assembly and transcriptome of the green algaChromochloris zofingiensisilluminates astaxanthin production

Abstract: Microalgae have potential to help meet energy and food demands without exacerbating environmental problems. There is interest in the unicellular green alga Chromochloris zofingiensis, because it produces lipids for biofuels and a highly valuable carotenoid nutraceutical, astaxanthin. To advance understanding of its biology and facilitate commercial development, we present a C. zofingiensis chromosome-level nuclear genome, organelle genomes, and transcriptome from diverse growth conditions. The assembly, derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
222
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(241 citation statements)
references
References 57 publications
12
222
1
1
Order By: Relevance
“…Nevertheless, we found that the maximum density of LINE elements coincided with the centromeres identified based on Marey maps and DNA methylation status in almost all (six out of the eight) LGs. Besides P. patens, this is also similar to some algal genomes, in which specific LINE elements were proposed to mark centromeric regions (Blanc et al, 2012;Roth et al, 2017). Taken together, our findings suggest that bryophyte centromeres are not characterized by the high abundance of typical centromeric repeat arrays but rather the accumulation of specific retrotransposons.…”
Section: Telomeric Tandem Repeat Arrays Are Shortsupporting
confidence: 79%
“…Nevertheless, we found that the maximum density of LINE elements coincided with the centromeres identified based on Marey maps and DNA methylation status in almost all (six out of the eight) LGs. Besides P. patens, this is also similar to some algal genomes, in which specific LINE elements were proposed to mark centromeric regions (Blanc et al, 2012;Roth et al, 2017). Taken together, our findings suggest that bryophyte centromeres are not characterized by the high abundance of typical centromeric repeat arrays but rather the accumulation of specific retrotransposons.…”
Section: Telomeric Tandem Repeat Arrays Are Shortsupporting
confidence: 79%
“…The alga is also able to synthesize high-value ketocarotenoids and is thought to be a candidate astaxanthin producer alternative to Haematococcus pluvialis [16]. The robustness in concurrent accumulation of TAG and astaxanthin [11,14,17] and availability of chromosome-level genome sequence [18] enable C. zofingiensis as an emerging model alga for both fundamental studies and industrial applications. While many studies deal with the engineering of culture conditions for TAG and astaxanthin production by C. zofingiensis [9,11,12,14,17,[19][20][21][22], the molecular mechanisms underlying their biosynthesis are less touched and remain to be fully explored in a system-level manner.…”
Section: Introductionmentioning
confidence: 99%
“…shown that the centromeric repeats in the Chlorophyceae species Chromochloris zofingiensis 383 consist of LTR elements from the Copia superfamily (Roth et al 2017). Secondly, the apparent 384 absence of ZeppL elements from Y. unicocca and V. carteri suggest that these elements are not 385 required for centromere formation in these species.…”
mentioning
confidence: 99%